Effects of Winding Attachment Positions on Output Characteristics of Flux‐Modulating Synchronous Machines. Issue 3 (May 2015) - Aoki, Hirofumi; Fukami, Tadashi; Shima, Kazuo; Tsuda, Toshihiro; Kawamura, Mitsuhiro
SUMMARY The flux‐modulating synchronous machine (FMSM) is a new type of multipole SM with nonoverlapping concentrated armature and field windings on the stator. This paper compares the output characteristics of two FMSMs through finite element analysis (FEA) and experiments. In both of the FMSMs, the attachment positions of the armature and field windings are swapped. To determine the reason for the discrepancies in their output characteristics, unsaturated inductances were calculated using a d‐‐q equivalent circuit. In addition, the calculated results of the inductances were confirmed through a visualization of the leakage fluxes using FEA. The results of the study show that the synchronous inductance can be reduced by attaching the armature winding to the air‐gap side of the stator teeth and that the reduction leads to an increase in output power.